Influence of Shod and Barefoot Running on the In Vivo Kinematics of the First Metatarsophalangeal Joint - Zhang, Faning; Ye, Dongqiang; Zhang, Xini; Sun, Xiaole; Zhang, Shen; Wang, Shaobai; Fu, Weijie (Frontiers in Bioengineering and Biotechnology, 2022)
The biomechanics of the first metatarsophalangeal joint (MTPJ) are affected by different shoe conditions. In the biomechanical research field, traditional skin-marker motion capture cannot easily acquire the in vivo joint kinematics of the first MTPJ in shoes. Thus, the present study aims to investigate the differences of the first MTPJ’s six degree-of-freedom (6DOF) kinematics between shod and barefoot running by using a high-speed dual fluoroscopic imaging system (DFIS). Fifteen healthy male runners were recruited. Computed tomography scans were taken from each participant’s right foot for the construction of 3D models and local coordinate systems. Radiographic images were acquired at 100 Hz while the participants ran at a speed of 3 m/s±5% in shod and barefoot conditions along with an elevated runway, and 6DOF kinematics of the first MTPJ were calculated by 2D–3D registration. Paired sample t-tests were used to compare the kinematic characteristics of the first MTPJ 6DOF kinematics during the stance phase between shod and barefoot conditions. Compared with barefoot, wearing shoes showed significant changes (p < 0.05): 1) the first MTPJ moved less inferior at 50%, but moved less superior at 90% and 100% of the stance phase; 2) the peak medial, posterior, and superior translation of the first MTPJ significantly decreased in the shod condition; 3) the extension angle of the first MTPJ was larger at 30%–60%, but smaller at 90% and 100% of the stance phase; 4) the maximum extension angle, and flexion/extension range of motion of the first MTPJ were reduced; 5) the minimum extension and adduction angle of the first MTPJ was increased in the shod condition. On the basis of the high-speed DFIS, the above results indicated that wearing shoes limited the first MTPJ flexion and extension movement and increased the adduction angle, suggesting that shoes may affect the propulsion of the first MTPJ and increase the risk of hallux valgus.